'A recipe for cultural disaster!'- a case study of Woolworths Group's proposal to build an alcohol megastore in Darwin, Northern Territory - Alessandro Connor Crocetti; Beau Cubillo (Larrakia); Troy Walker (Yorta Yorta); Fiona Mitchell (Mununjali); Yin Paradies (Wakaya); Kathryn Backholer; Jennifer Browne (BMC, 2023)
Abstract Background The health and wellbeing impacts of commercial activity on Indigenous populations is an emerging field of research. The alcohol industry is a key driver of health and social harms within Australia. In 2016 Woolworths, the largest food and beverage retailer in Australia, proposed to build a Dan Murphy's alcohol megastore in Darwin, near three 'dry' Aboriginal communities. This study examines the tactics used by Woolworths to advance the Dan Murphy's proposal and understand how civil society action can overcome powerful commercial interests to protect Aboriginal and Torres Strait Islander health and wellbeing. Methods Data from 11 interviews with Aboriginal and non-Aboriginal informants were combined with data extracted from media articles and government, non-government and industry documents. Thematic analysis was informed by an adapted corporate health impact assessment framework. Results Woolworths employed several strategies including lobbying, political pressure, litigation, and divisive public rhetoric, while ignoring the evidence suggesting the store would increase alcohol-related harm. The advocacy campaign against the proposal highlighted the importance of Aboriginal and non-Aboriginal groups working together to counter commercial interests and the need to champion Aboriginal leadership. Advocacy strategies included elevating the voices of community Elders in the media and corporate activism via Woolworths' investors. Conclusions The strategies used by the coalition of Aboriginal and non-Aboriginal groups may be useful in future advocacy campaigns to safeguard Aboriginal and Torres Strait Islander health and wellbeing from commercial interests.